Implementing effective information technology in education: an examination of the leadership and management needs of schools. - Selwood, Stuart (Curtin University, 2000)
This study focuses on the need for more attention to be given to the leadership and management issues associated with the increased adoption of Information Technology tools by schools. The genesis of the study began with the development of the Advanced Diploma of Information Technology in Education (ADITE) as a qualification designed for people who were or who aspired to become the leaders of IT in their schools. Apart from the work associated with the development and delivery of this programme, research activity also included in-depth interviews with school principals and Chief Information Officers (CI0s). A survey of school IT leaders was also conducted and the results of this were compared with the results of a similar survey conducted in North America among CIOs. Further detailed data were obtained over a period of two and a half years when the author took up a position as the Head of Department - Information Technology at a prominent New Zealand secondary school. A major intention of the project was to make comparisons between the management and administration of Information Technology in business with that in education.There are at least two significant aspects to this study. It is one of the few so undertaken that focuses on area of the leadership and management of IT in schools and it is perhaps unique in its endeavour to draw from both business and educational experiences. The study concludes that there is much to be gained by schools adopting more professional approach to the management and administration of their IT equip and infrastructure, and emphasises the importance of the leadership role that the people charged with these sorts of responsibilities must adopt.